Intrahepatic Biliary Cystadenoma: A Case Report - Kulaçoğlu, Sezer; Arık, Deniz; Han, Özge (Fırat University, 2012)
Primary hepatic cystic neoplasms are rare in surgical pathology practice. Biliary cystadenoma is the most frequent of them. It seems generally in middle aged women and has characteristic histopathologic stromal features. These tumors grows slowly but recurrence is seen by incomplet resection. Because of malignant transformations risk total excision is required. Thirtyfive years-old female presented with abdominal pain on right upper quadrant and multilocular cystic lesion in 7 cm dimension is demonstrated by radiologic evaluation. After surgical excision and histopathologic examination it was diagnosed as biliary cystadenoma. In this paper histopathologic features were discussed with the literature findings.

Cerrahi patoloji pratiğinde karaciğerin primer kistik neoplazmları nadir olmakla birlikte, biliyer kistadenom bunların en sık görülenidir. Biliyer kistadenom, orta-yaş kadınlarda görülen, histopatolojik stromal özellikleri dikkati çekici tümörlerdir. Yavaş büyüme eğiliminde olan bu tümörlerde yetersiz eksizyon sonucu rekürrens gelişebilmesi ve nadiren de olsa malign transformasyon görülebilmesi nedeniyle lezyonun total eksizyonunun gerektiği vurgulanmaktadır. Burada karın sağ üst kadranında ağrı şikayeti ile hastanemize başvuran, radyolojik olarak karaciğer sağ lobunda 7 cm çapında multiloküler kistik kitle saptanan, cerrahi eksizyon ve histopatolojik inceleme sonrası biliyer kistadenom tanısı alan 35 yaşında kadın hasta sunulmaktadır. Olgunun histopatolojik özellikleri literatür bilgileri eşliğinde tartışılmıştır.
İntrahepatik Biliyer Kistadenom: Olgu Sunumu